1999
DOI: 10.1046/j.1365-3008.1999.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wildfires on the megafauna of Emas National Park, central Brazil

Abstract: This study evaluates the impact of two wildfires, in 1994 and 1995, on the large mammal fauna of Emas National Park, central Brazil. The 1994 fire burned 100 per cent of the park's grassland and after the fire, in a c. 2000‐ha survey area, the authors found 16 giant anteaters Myrmecophaga tridactyla, two giant armadillos Priodontes maximus and one tapir Tapirus terrestris that had died in the fire. The 1995 fire burned 15 per cent of the park's grassland and no dead animals were found in a 220‐ha survey area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 11 publications
0
34
0
3
Order By: Relevance
“…This type of fire can have catastrophic effects on the local fauna (Ramos-Neto and Pivello 2000). At Emas National Park, Silveira et al (1999) observed that a high-intensity fire caused negative effects on mammal populations. A second fire, in the following year with less biomass to burn, was less intense, and its effects were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This type of fire can have catastrophic effects on the local fauna (Ramos-Neto and Pivello 2000). At Emas National Park, Silveira et al (1999) observed that a high-intensity fire caused negative effects on mammal populations. A second fire, in the following year with less biomass to burn, was less intense, and its effects were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to biodiversity losses due to vegetation encroachment (Coutinho 1990 for plants; Andersen, Hertog & Woinarski 2006 for ants in Australian savannas), suppression of fires for long periods has been reported to cause high-intensity wildfires due to accumulation of large amounts of inflammable material (Keeley, Fotheringham & Morais 1999), causing high greenhouse gas emissions (Russell-Smith et al 2009) and biodiversity losses (Silveira et al 1999). The consequences of wildfires can be particularly negative in fragmented landscapes, where the habitat as a whole can be simultaneously burned, hindering the escape of animals to unburned sites and temporarily eliminating all sources of food for primary consumers.…”
Section: The Consequences Of Fire Suppressionmentioning
confidence: 99%
“…At present, controlled fires can be legally applied only to a few protected areas whose management plans include prescribed burning. All remaining Cerrado areas in private properties are prohibited from using fire and are therefore subjected to the consequences of vegetation encroachment (Coutinho 1990;Durigan & Ratter 2006;Scott et al 2012) or of uncontrolled and high-intensity wildfires (Keeley, Fotheringham & Morais 1999;Silveira et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A ocupação humana em diversos habitats acarreta o aumento na incidência do atropelamento de animais selvagens (Fischer 1997), caça predatória (Leuwenberg 1997) e incêndios florestais (Silveira et al 1999), com isso os animais de vida livre sofrem traumas cutâneos, nervosos, vasculares, musculares e ósseos, fazendo-se necessário o conhecimento da morfologia da espécie para o tratamento clinico-cirúrgico dessas lesões.…”
Section: Introductionunclassified